Effects of Seaweed and Organic Mineral Supplementation on Nutrient Digestibility and Milk Yield in Lactating Saanen Crossbred Goats - Prayitno, Caribu Hadi; Sarwanto, Doso; Setiadi, Deni (Buletin Peternakan, 2025)
Dairy goat productivity in Indonesia remains relatively low, primarily due to its suboptimal feed efficiency, affecting nutrient digestibility and milk yield. This study aimed to evaluate the effects of seaweed and organic mineral supplementation on feed intake, nutrient digestibility, and milk production performance in dairy goats. An in vivo experimental study was conducted using a completely randomized design involving 16 pregnant Saanen-Etawah crossbred ewes in their second lactation and offered treatment feeds for 4 weeks before parturition until 8 weeks postpartum. The animals divided into four dietary treatments: T0 (control diet without supplementation), T1 (control diet + rumensin), T2 (control diet + 2% seaweed), and T3 (T2 + organic minerals including Cr, Se, and Zn) with the feed offered was based on dry matter requirements of 4% of body weight, once daily at 1.30 p.m. The control diet is a mixture of concentrate, tofu dregs, and forage. The observed parameters included dry matter intake (DMI), organic matter intake (OMI), digestibility of dry matter, organic matter, crude fiber, and crude protein, as well as daily milk yield and its components. The results indicated that while feed intake did not differ significantly among treatments, the supplementation of seaweed and organic minerals significantly improved nutrient digestibility, daily milk yield, and the composition of milk, including fat, protein, lactose, and total solids. The T3 treatment yielded the most optimal outcomes in enhancing feed conversion efficiency and milk performance. These results suggest that seaweed and organic minerals may serve as effective and applicable functional feed additives to sustainably improve dairy goat productivity through optimized rumen function and metabolic utilization.